Stationary in the Office: Emerging themes for active buildings - McGann, Sarah; Creagh, Robyn; Tye, Marian; Jancey, Jonine; Blackford, Krysten (Routledge, 2014)
This research aims to highlight the gap between management, design and health-promotion strategies in the workplace, and seeks to illustrate how the disciplines of architecture and health promotion can work together to reduce sedentary behaviour and increase opportunities for incidental physical activity within the working day. In particular, this paper argues that qualitative research with a focus on socio-cultural factors is necessary to fully understand how the spatial practices of a workplace might positively or negatively influence the sedentary behaviour of workers. This paper summarizes observational and anecdotal findings of a pilot study. The workplace was analysed using architectural movement diagramming, observational and photographic studies along with textural analysis of the anecdotal comments offered to the field officers during the process of data collection. This study shows that overlaying physical workplace design are multiple layers of spatial, managerial and cultural influences that affect workers and their reasons for movement. The lived-experience information gained from the observational studies adds to a richer understanding of the workplace as a social organization and how this might inform active workplace design.